Specifics of Digital Interaction of Regional Mass Media with Audience: Nizhny Novgorod Experience - A. L. Kodanina; T. E. Novikova; M. A. Savelyeva (Научный диалог, 2023)
The focus of the authors of the article attention is the analysis of the practical experience of mastering digital media technologies aimed at the formation and strengthening of constructive interaction with the readership. The subject of analysis was the sites and social networks of traditional mass media of the closed administrative-territorial formation (ZATO) of Sarov (Nizhegorod region). These sources were studied in terms of the specifics of digital content distribution, the formation of new technological approaches to interaction with the audience, and the search for creative ways of establishing constructive interaction with the reader. It has been established that the use of digital technologies in the local information market has not yet become a universal trend. At the same time, it is noted that the analysis of the activity of regional mass media in social networks, video hosting, messengers revealed positive practices of interaction with audience groups, in particular, a clearly noticeable tendency to establish interactive communication with the target audience. However, conclusions are drawn about the insufficient use of available communication resources in building a mutually interested dialogue, which in the future may negatively affect the prospective development of the local press, lead to stagnation due to inattention to the requests and expectations of the audience.